2016
DOI: 10.1016/j.visres.2015.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Can two dots form a Gestalt? Measuring emergent features with the capacity coefficient

Abstract: DOTS AbstractWhile there is widespread agreement among vision researchers on the importance of some local aspects of visual stimuli, such as hue and intensity, there is no general consensus on a full set of basic sources of information used in perceptual tasks. Gestalt theories place particular value on emergent features, which are based on the higher-order relationships among elements of a stimulus rather than local properties. Thus, arbitrating between di erent accounts of features is an important step in ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 47 publications
5
27
0
Order By: Relevance
“…But if that is true, then, how and when do they differ? Relying only on discrimination accuracies, reaction times and processing capacity 8 , 21 has not allowed us to answer this question so far. Experimental phenomenology 22 also does not seem to suffice.…”
Section: Introductionmentioning
confidence: 99%
“…But if that is true, then, how and when do they differ? Relying only on discrimination accuracies, reaction times and processing capacity 8 , 21 has not allowed us to answer this question so far. Experimental phenomenology 22 also does not seem to suffice.…”
Section: Introductionmentioning
confidence: 99%
“…. For example, Garner and Felfoldy (1970) have shown that dots separated in space but arranged in a Bgood configural formâ re processed as integral dimensions (see also Hawkins, Houpt, Eidels, & Townsend, 2016). Fitousi and Algom (2006) have shown that numerical Stroop dimensions that are separated in space interfere with each other (see also Kahneman & Chajczyk, 1983).…”
Section: Qualitative Model Predictionsmentioning
confidence: 99%
“…Deciding on the specific spatial arrangement of the dots in the stimulus display is complicated by two issues. First, increasing the number of dots in a display gives rise to new emergent features (Pomerantz & Portillo, 2011;Hawkins, Houpt, Eidels, & Townsend, 2016). For example, moving from a one dot-display to two dots adds not only an additional dot, but also new information concerning the relative position and distance between the two dots.…”
Section: The Language Of Numbersmentioning
confidence: 99%